2019
DOI: 10.1186/s12978-019-0703-z
|View full text |Cite
|
Sign up to set email alerts
|

Birth preparedness and complication readiness practice and influencing factors among women in Sodo town, Wolaita zone, Southern Ethiopia, 2018; community based cross-sectional study

Abstract: Background Birth preparedness and complication readiness (BPCR) is a strategy that helps women to consider all available maternal health care services during pregnancy and prepare for potential complications. Though global annual number of maternal deaths decreased to an estimated 303,000 in 2015, avoidable morbidity and mortality remains a formidable challenge in many developing countries which account for approximately 99% (302,000) of the global maternal deaths in 2015. This study aims to asses… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

12
40
5

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 27 publications
(58 citation statements)
references
References 21 publications
12
40
5
Order By: Relevance
“…This study reveals that the practice of birth preparedness and complication readiness was (48.6%) (95% CI: 46.9%, 49.8%). Reported in the present study is in line with the study done in Wolaita Sodo town southern Ethiopia (8) and in rural community in southern Nigeria 48.4% (15). The similarity may be due to similarity in methodology and socio-demographic characteristics.…”
Section: Discussionsupporting
confidence: 90%
See 4 more Smart Citations
“…This study reveals that the practice of birth preparedness and complication readiness was (48.6%) (95% CI: 46.9%, 49.8%). Reported in the present study is in line with the study done in Wolaita Sodo town southern Ethiopia (8) and in rural community in southern Nigeria 48.4% (15). The similarity may be due to similarity in methodology and socio-demographic characteristics.…”
Section: Discussionsupporting
confidence: 90%
“…The possible reason is that younger women may have no previous obstetrics complication that makes them to prepare themselves but the old women they have a history of obstetrics complication they prepare themselves for their current pregnancy (not assessed in study). This study nding differ from study conducted in Wolaita Zone, Sodo town, that indicated younger age groups are more likely to birth preparedness and complication readiness practice (12). The observed difference might be because of older women in Sodo town may be traditional and they might accept as they feel safe as they deliver at home and the older women are less likely to birth preparedness and complication readiness.…”
Section: Discussioncontrasting
confidence: 89%
See 3 more Smart Citations